cAMP Signaling in Pathobiology of Alcohol Associated Liver Disease - Mohamed Elnagdy; Shirish Barve; Craig McClain; Leila Gobejishvili (Biomolecules, 2020)
The importance of cyclic adenosine monophosphate (cAMP) in cellular responses to extracellular signals is well established. Many years after discovery, our understanding of the intricacy of cAMP signaling has improved dramatically. Multiple layers of regulation exist to ensure the specificity of cellular cAMP signaling. Hence, disturbances in cAMP homeostasis could arise at multiple levels, from changes in G protein coupled receptors and production of cAMP to the rate of degradation by phosphodiesterases. cAMP signaling plays critical roles in metabolism, inflammation and development of fibrosis in several tissues. Alcohol-associated liver disease (ALD) is a multifactorial condition ranging from a simple steatosis to steatohepatitis and fibrosis and ultimately cirrhosis, which might lead to hepatocellular cancer. To date, there is no FDA-approved therapy for ALD. Hence, identifying the targets for the treatment of ALD is an important undertaking. Several human studies have reported the changes in cAMP homeostasis in relation to alcohol use disorders. cAMP signaling has also been extensively studied in in vitro and in vivo models of ALD. This review focuses on the role of cAMP in the pathobiology of ALD with emphasis on the therapeutic potential of targeting cAMP signaling for the treatment of various stages of ALD.